Celebrating Romans: template for Pauline theology - Jewett, Robert; McGinn, Sheila E. (William B. Eerdmans Pub, 2004)
This book brings international Christian scholars together to celebrate Robert Jewett's lifelong interest in Romans by reviewing - and significantly advancing - five fruitful approaches to Paul's most influential work. The authors, all established teachers in academic and church settings, recognize the need for analyses of the Bible that are substantial and scholarly but also intelligible to nonspecialists. The essays in Celebrating Romans will challenge the thinking of students and scholars alike, illuminating diverse methods of biblical analysis and fostering a deeper appreciation for and engagement with this crowning literary achievement of the apostle to the Gentiles.